Perception, experience and body identity. - López-Ibor, Juan J.; Ortiz, Tomás; López-Ibor, María I. (Actas Espanolas de Psiquiatria)
The physician has to know the patient in the disease and not only the disease in the patient, from the dual perspective of the body as object and the body as subject. This also affects the patient who has to cope with the reality of having a body that bursts into the subject's consciousness as a vital threat, as source of discomfort and inability and being a body (Marcel). The human body in its dual aspect has been and is a great unknown, if not a great outrage in spite of the fact that we are our body and our body is each of us. We sometimes do not feel as we are and thus a confrontation arises, sometimes more normal, others more morbid. This forces the physician to face complex ethics considerations and the scientist to accept a personal identity disorder. Dualism considers that there are two substances in us, one that distinguishes us from other beings and from the rest of the individuals of the human species, the soul, the psychic life, mind or consciousness, and another more insubstancial one, the body. The aim of the first substance is to dominate the body, to survive it after death when it is, already a corpse is meant to become putrefied, is buried, incinerated or thrown to the depth of the sea. This dualism aims to explain the origin of the evil and the attitude to defeat it and it does so efficiently. This anthropology has very ancient roots (the Upvanishads, in the orphic texts, in Plato), it is the core of Gnostic thought and the foundation of the modern science since Descartes. Some monist perspectives are a masked dualism or a mereologic fallacy, according to which, the brain is conscious, when that what is conscious is the subject, although the subject, with the brain could not be conscious. Therefore, a new perspective is proposed, chiasmatic or janicular monism, that considers the adaptive value of focusing on the reality from two perspectives, as physical universe and the world of interpersonal relationships. In the agnosias and in the phantom limb there is a confrontation between the body object and the body subject that has made it possible to investigate how the perception of the own body is and how the brain generates the schema and the body image. The study of the body experience, from the phenomenology and the anthropological psychiatry perspective, has made it possible to go greater in-depth into the knowledge of the alterations of the experience of the own body in different mental diseases, especially in those in which a confrontation between the body and the personal identity arises makes it necessary to consider the process of individual identification and a category of personal identity disorders that would include body dysmorphic disorder, erythrophobia, anorexia nervosa, body integrity identity as well as the gender-type disorders (transsexualism, nonfetishistic transvestism, gender identity disorder during childhood).